Microalbuminuria among children with congenital heart disease seen in Sokoto, North-Western Nigeria - Isezuo, Khadijat O.; Sani, Usman M.; Waziri, Usman M.; Ilah, Bilkisu G.; Jiya, Fatima B.; Abdulrahman, Muhammad B.; Hano, Ibrahim J. (International Journal of Contemporary Pediatrics, 2021)
Background: Congenital heart disease (CHD) especially cyanotic CHD has been associated with microalbuminuria which is an early marker of glomerular nephropathy but this has hardly been studied in African children. The aim of this study was to compare mean microalbuminuria levels and associations among children with acyanotic CHD, cyanotic CHD and normal controls. Methods: Forty-one (41) children comprising 19 acyanotic CHD, 14 cyanotic CHD and 8 without CHD aged 1 to 15 years were recruited in a cross-sectional study. Quantitative urinary microalbuminuria was measured by ELISA technique. Positive result was microalbuminuria of 30-300 mcg/mgCr. Mean levels were compared by student t-test and analysis of variance (ANOVA). Statistical significance was taken at p<0.05. Results: There were 22 (53.7%) females and 19 (46.3%) males. Mean level of microalbuminuria was highest in those with cyanotic CHD at 147.7±78.8 mcg/mgCr, followed by those with acyanotic CHD at 111.8±61.5 mcg/mgCr and lowest in those without CHD at 67.3±31.6 mcg/mgCr. There was significant difference between the groups with CHD and those without CHD (F=4.1, p=0.03) and microalbuminuria had a significant but weak negative correlation with oxygen saturation implying that microalbuminuria increased with worsening cyanosis. Conclusions: Microalbuminuria was high among the patients with CHD, though higher in cyanotic patients warranting closer follow up of these patients.